The Association of Oxidative Stress Status with Open-Angle Glaucoma and Exfoliation Glaucoma: A Systematic Review and Meta-Analysis - Binghua Tang; Shengjie Li; Wenjun Cao; Xinghuai Sun (Journal of Ophthalmology)
Purpose. To systematically evaluate the associations between oxidative stress status and different types of glaucoma. Design. Systematic review and meta-analysis. Methods. We searched PubMed, EMBASE, and the Web of Science for randomized controlled trials written in the English language between January 1, 1990, and November 30, 2016. A random effects model was used to estimate oxidative stress status along with weighted mean differences and 95% confidence intervals (CIs). A funnel plot analysis and Egger’s test were performed to assess potential publication bias. Main outcome measures. Oxidative stress status was abnormal and different in patients with OAG (open-angle glaucoma) and EXG (exfoliation glaucoma). Results. Blood TAS (total antioxidant status) was lower in the OAG group than in the control group, with a mean difference of 0.580 mmol/L (p<0.0001, 95% CI = −0.668 to −0.492). The aqueous humor SOD (superoxide dismutase), GPX (glutathione peroxidase), and CAT (catalase) levels were higher in the OAG group than in the control group, with mean differences of 17.989 U/mL (p<0.0001, 95% CI = 14.579–21.298), 12.441 U/mL (p<0.0001, 95% CI = 10.423–14.459), and 1.229 fmol/mL (p=0.042, 95% CI = 0.043–2.414), respectively. Blood TAS was lower in the EXG group than in the control group, with a mean difference of 0.262 mmol/L (p<0.0001, 95% CI = −0.393 to −0.132). However, there were no differences in blood TOS and aqueous humor TOS between the EXG group and the control group. Conclusions. This meta-analysis indicates that OAG patients had a lower TAS in the blood and higher levels of SOD, GPX, and CAT in the aqueous humor, while EXG patients only had a decreased TAS in the blood.